Measurement of electroweak production of two jets in association with a Z boson in proton-proton collisions at $\sqrt{s}=8\,\text {TeV}$ - CMS collaboration (2146 authors) (2015)
The purely electroweak (EW) cross section for the production of two jets in association with a Z boson, in proton–proton collisions at $\sqrt{s}=8\,\text {TeV}$ , is measured using data recorded by the CMS experiment at the CERN LHC, corresponding to an integrated luminosity of 19.7 $\,\text {fb}^\text {-1}$ . The electroweak cross section for the $\ell \ell jj$ final state (with $\ell = e$ or $μ $ and j representing the quarks produced in the hard interaction) in the kinematic region defined by $M_{\ell \ell } >50$ $\,\text {GeV}$ , $M_jj >120$ $\,\text {GeV}$ , transverse momentum $p_T j> 25$ $\,\text {GeV}$ , and pseudorapidity $|η _j |< 5$ , is found to be $σ _EW(\ell \ell jj)=174 ± 15\,\text {(stat)}± 40\,\text {(syst)}\text {\,fb}$ , in agreement with the standard model prediction. The associated jet activity of the selected events is studied, in particular in a signal-enriched region of phase space, and the measurements are found to be in agreement with QCD predictions.